The Failure to Execute Inkracht Verdicts: Political Protection, Legal Manipulation, and the Erosion of the Rule of Law: Gagalnya Eksekusi Putusan Inkracht: Proteksi Politik, Manipulasi Hukum, dan Erosi Wibawa Negara Hukum - Fahriza Hafiz (Journal of Law, Human Rights, Immigration, and Corrections, 2025)
This study critically analyzes the failure to execute a final and binding criminal verdict (inkracht) in Indonesia, focusing on the high-profile case of Silfester Matutina (Supreme Court Decision No. 287 K/Pid/2019). Despite the verdict's finality since 2019, its non-execution until 2025 a six-year delay represents a fatal legal anomaly. Employing Gustav Radbruch’s Trias of Legal Values, the analysis reveals that the core principles of Legal Certainty (Rechtssicherheit) and Justice (Gerechtigkeit) have been subverted by a distorted notion of Expediency (Zweckmäßigkeit) serving political or group interests. The failure by the Prosecutor's Office to immediately execute the condemnatoir judgment, coupled with the erroneous tolerance of a non-suspensory appeal (Peninjauan Kembali), points to institutional collusion and political protection. The appointment of the convicted person as a BUMN Commissioner further exemplifies this 'sharp downwards, blunt upwards' justice. This systemic failure erodes judicial authority, undermines the rule of law, and creates a precedent of impunity, necessitating urgent institutional reform and strict accountability for state law enforcement.